Influencia del clima laboral en la presencia de estrés en los trabajadores de la empresa pesquera hayduk, distrito de chimbote - provincia del santa: 2014 - Romero Quilcate, Isabel Jackeline (2015)
This research study was conducted in the business of fishing category, aims to present and described how it turns influence the working environment in the presence of stress in workers fishery Hayduk, Chimbote District - Province Santa: 2014, this work was conducted with a sample of 226 workers between the ages of 25 years more. Note that has been made known through their testimonies of life situations, facts, and events that arose on a personal level, this way, the thesis quantitative and qualitative data are provided for this purpose various methods were applied techniques like observation, interviews, surveys, and bibliography used to find information about the influence of the working environment in the presence of stress in workers, and instruments that allowed collecting significant events of the problematic reality show. Through statistical method situation that leads to the existence of occupational stress was reached to have clarity of reality in which the study group is shown to occur workload in the intervention group, even arising from so slight but constant. In the first chapter the theoretical framework where the working environment and work stress on the second item problem formulation, hypothesis, objectives and the sample which intervened, second in the third chapter presents conceptualized addresses analysis and interpretation of presentation of the results obtained from data collected during the development of research through surveys (test) applied to workers fishery Hayduk, also in the fourth chapter is presented is given to know the answer to the analysis of data and results and discussion of results.